Taxonomic revision and identification keys for the giant honey bees - Kitnya, Nyaton; Brockmann, Axel; Otis, Gard W. (Frontiers in Bee Science, 2024)
Introduction The taxonomy and phylogeny of the giant honey bees (Apis; subgenus Megapis) remain controversial and unresolved. The species boundaries within the subgenus are unclear, and some species that are recognized on the basis of genetic differences lack supporting morphological characteristics. Two species are now well accepted: Apis dorsata Fabricius, 1793, of tropical regions of Asia, and Apis laboriosa Moore et al., 1871, an inhabitant of the foothills of the Himalayas and neighboring mountain ranges. In addition, researchers have suggested that the two allopatric populations of giant honey bees that inhabit Sulawesi, Indonesia (Apis binghami Cockerell, 1906) and the oceanic Philippine islands (Apis breviligula Maa, 1953), as well as the South Indian form also deserve species status. We evaluated morphological characters of all of these taxa in order to revise the taxonomy of the subgenus. Methods We conducted a taxonomic study based on morphological characters of Megapis from throughout Asia. In addition, we created taxonomic keys to workers and drones for the giant honey bee species that we recognize. Results Our study confirms that A. laboriosa is a distinct species based on numerous morphological characters. Moreover, A. dorsata of mainland Asia differs from the two island taxa based on coloration, ocellus size, and the spacing of compound eyes and ocelli. We found no evidence that breviligula of the Philippines has a distinctively short tongue. Moreover, we detected only one minor character (the shape of sternum 5) that differed statistically between bees from Sulawesi and the Philippines. We conclude that the bees from these islands represent a single morphological species, A. binghami, with two subspecies, A. b. binghami and A. b. breviligula. A. dorsata from the Andaman Islands are smaller than but conspecific with dorsata of mainland Asia. We found no morphological autapomorphies in the giant honey bees of southern India that are known to differ in mtDNA from A. dorsata from elsewhere in mainland Asia. Discussion Our morphological examination of Megapis specimens firmly supports three species of giant honey bees: A. laboriosa, A. dorsata, and A. binghami. More detailed examination of specimens is required to reconcile our three morphological species with the five clades that have been identified with genetic analyses.